Development of Creative Play-Based Badminton Service Learning Model for Elementary School Students - Fadillah, Arman; Hernawan; Asmawi, Moch. (Indonesian Journal of Sport Management, 2025)
This study aims to develop a creative play-based learning model for badminton tailored for elementary school students, focusing on the analysis of the development process, feasibility, and effectiveness of the model. The research was conducted in educational institutions in East Jakarta and South Jakarta, involving 60 upper-grade elementary school students as participants, using a Research and Development (R&D) approach with the ADDIE model. 1) The developed model integrates basic badminton serve techniques with creative play concepts, designed to align with the characteristics of 10–12-year-old students. 2) The validation process resulted in 16 learning models with specific objectives, appropriate media, and detailed implementation steps. 3) Effectiveness testing using the pretest-posttest design demonstrated a significant improvement in badminton serve skills, with the experimental group’s average score increasing from 7.47 to 15.63 and an N-gain score of 0.78 (high category). A significance value of 0.000 indicates the model's effectiveness in enhancing badminton service skills while providing an interactive, enjoyable, and effective learning experience.